2021
DOI: 10.3389/fnins.2021.684926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Pain Treatment on Altered Functional and Metabolic Activities in the Brain: A Systematic Review and Meta-Analysis of Functional Neuroimaging Studies

Abstract: Previous studies have identified altered brain changes in chronic pain patients, however, it remains unclear whether these changes are reversible. We summarized the neural and molecular changes in patients with chronic pain and employed a meta-analysis approach to quantify the changes. We included 75 studies and 11 of these 75 studies were included in the activation likelihood estimation (ALE) analysis. In the 62 functional magnetic resonance imaging (fMRI) studies, the primary somatosensory and motor cortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 126 publications
1
12
0
Order By: Relevance
“…It is generally recognized that chronic exposure to pain increases pain sensitivity through central sensitization, an excessive responsiveness to pain in the nociceptive pathway. 22,34 Our results seemed to support this relationship with a higher measured sensitivity pain in participants reporting pain and pain medication usage, but also in older participants and participants reporting multiple pains. However, it has also been reported that pain tolerance in patients with acute pain could increase via selfinduced positive expectancies or cognitive-behavioral therapy.…”
Section: Discussionsupporting
confidence: 64%
“…It is generally recognized that chronic exposure to pain increases pain sensitivity through central sensitization, an excessive responsiveness to pain in the nociceptive pathway. 22,34 Our results seemed to support this relationship with a higher measured sensitivity pain in participants reporting pain and pain medication usage, but also in older participants and participants reporting multiple pains. However, it has also been reported that pain tolerance in patients with acute pain could increase via selfinduced positive expectancies or cognitive-behavioral therapy.…”
Section: Discussionsupporting
confidence: 64%
“…The transmission of pain in the central nervous system is highly complicated and involves multiple brain regions (Kim et al., 2021; Qi et al., 2018). In this study, we investigated the underlying neurobiology of postoperative acute pain and the modulatory effect of EA on acute pain after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…A double-blind randomized study found that 40% of NeuP patients are able to achieve remission with the use of motor cortex stimulation via surgically implanted electrodes ( 60 ). A systematic review and meta-analysis of fMRI studies also found that the motor cortex of such patients exhibited significantly decreased activity after treatments as compared to baseline ( 40 ).…”
Section: Discussionmentioning
confidence: 99%